Effect of Adding Nitrogen Mixed With The Radon Gas Line and ‎Roasting The Mixture For Production The Final Interactive Positive ‎Results (Journal of University of Babylon for Engineering Sciences, 2023)
Design this industrial model aim to reduce the radon radioactive gas concentration which depending on the mixing of many reactive gases like, hydrogen  which explosion when mixing with oxygen by ratio of 2: 1,  nitrogen, oxygen and carbon dioxide gases with a single hydrocarbon manufactured through a generation of self-unit using the anaerobic digester process.  Use electronic detonator to obtain the partial explosion inside the combustion chamber which designed for this  purpose, use also dual thermal furnaces for obtaining  higher degrees than (650Co)  to reach the first ionization level energy which equals to (1037 kJ /mol), reaches this level helps radon gas to transfer from inactive status to interactive case with the found of potassium hydroxide and purified carbon materials. Use also many gauges to measure voltage,  heat, and power as well as to show the form of thermal shock which wave produced during the partial explosion processes. Use electronic thermal gauges at each stage of of this model. Effective cooling system used due to high temperatures at each stage as one of occupational safety devices. When doing all thermal processes, roasted the carburetor gas mixture through an ionization chambers with voltage exceeds than (1500 volts),  ionization chamber consists of two electrodes made of zinc for the purpose of conducting the decomposition ions to positive and  negative. Radon congregates at the anode and transfer to another material called carbonyl as a resinous substance, this material is has no any effect on human health. Results proved that there is a sharp decline in concentration after treatment more than 52% in air with standard deviation equal to (5.6), results also proved low concentration of gas in water more than (40%) after treatment with standard deviation equals to (7). This design has high economic feasibility in comparison with the cost of treatment of when exposure to this gas in the absence of treatment. Thermal shock chamber was used in the three test stages, cooling and heating systems were used through the work, in addition use multi measuring devices. Results showed decrease in the concentration of radon gas by (40%) after conducting a series of different treatment processes. The main objective of this research is to reduce the concentration of this gas through our system to treat areas polluted with this gas.